Schoolmasters of Karcag and Kisújszállás at Western European Universities and Academies Between the 17th and 19th Century - Éliás, János (Acta Neerlandica, 2022)
The aim of our paper is to discuss the significance of particle schools of Karcag and Kisújszállás in 18–19th century education history. Greater Cumania, the region that both towns are within, was almost 100% Calvinist since the Reformation, therefore, examining the influence of Calvinism on the region’s education is crucial. Our purpose is to introduce the schoolmaster’s office, the financial basis, and circumstances of going to Western European universities in the 18–19th centuries, since the schoolmasters of these two towns have not been investigated yet. Our research is based on primary (archival) sources, mainly Hungarian Reformed districtual, diocesan, and congregational documents, canonical visitation records, and protocols. Our paper also provides a detailed prosopography database of the schoolmasters of Karcag and Kisújszállás.